Predominant Role of Plasmacytoid Dendritic Cells in Stimulating Systemic Autoimmunity - Huang, Xinfang; Dorta-Estremera, Stephanie; Yao, Yihong; Shen, Nan; Cao, Wei (Frontiers in Immunology, 2015)
Plasmacytoid dendritic cells (pDCs), which are prominent type I interferon (IFN-I)-producing immune cells, have been extensively implicated in systemic lupus erythematosus (SLE). However, whether they participate critically in lupus pathogenesis remains unknown. Recent studies using various genetic and cell type-specific ablation strategies have demonstrated that pDCs play a pivotal role in the development of autoantibodies and the progression of lupus under diverse experimental conditions. The findings of several investigations highlight a notion that pDCs operate critically at the early stage of lupus development. In particular, pDCs have a profound effect on B-cell activation and humoral autoimmunity in vivo. This deeper understanding of the vital role of pDCs in lupus pathogenesis supports the therapeutic targeting of the pDC-IFN-I pathway in SLE.